2014
DOI: 10.1002/ejoc.201301739
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Access to α‐Substituted Functional Aspartic Acid Derivatives by a [3+2] Strategy Employing a Chiral Dienophile

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Interestingly, acyclic carboxy ketonitrones are found to display a pure and stable E geometry. Accordingly, high levels of stereocontrol were reported by our group in chiral auxiliarycontrolled thermal 1,3-DC reactions involving aspartic nitrones and vinyl ethers, 105,106 as well as in enantioselective cycloadditions involving alanine-containing nitrones and enals (Figure 10). 103,104 Recently, original studies about 1,3-DC performed through a "green protocol" have been reported such as the efficient synthesis of N-benzyl-fluoro-isoxazolidines 38 in ionic liquids described by Chakraborty et al 107 (Scheme 8).…”
Section: Chemical Reviewsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, acyclic carboxy ketonitrones are found to display a pure and stable E geometry. Accordingly, high levels of stereocontrol were reported by our group in chiral auxiliarycontrolled thermal 1,3-DC reactions involving aspartic nitrones and vinyl ethers, 105,106 as well as in enantioselective cycloadditions involving alanine-containing nitrones and enals (Figure 10). 103,104 Recently, original studies about 1,3-DC performed through a "green protocol" have been reported such as the efficient synthesis of N-benzyl-fluoro-isoxazolidines 38 in ionic liquids described by Chakraborty et al 107 (Scheme 8).…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…As a valuable exception, the use of appropriate hydrogen transfer conditions proved its efficiency to achieve N-debenzylation with respect to the isoxazolidine ring of adducts produced from N-benzyl carboxy ketonitrones. 93,106,118 Glycosylnitrones and tetrahydropyranosyl-substituted nitrones lead to N-protected isoxazolidines, which may be deprotected by acidic hydrolysis, and hydroxyaminolysis while leaving the N−O bond intact. 105,119−122 N-Benzhydryl nitrones were also reported to yield cycloadducts, which could be removed by NBS oxidation, 58 either in acidic conditions (HCl in MeOH) 62 or via a reductive cleavage with Et 3 SiH.…”
Section: Chemical Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…We showed previously that cleavage of the N–O bond could be achieved with reducing agents such as Mo(CO) 6 or SmI 2 when the nitrogen is equipped with an electron‐withdrawing group such as acetyl or trifluoroacetyl, giving access to the aldehyde or the ester 5. This reaction, which has been shown to be sensitive to steric hindrance,5c has never been done previously on isoxazolidines with an aminoacyl group on the nitrogen. When 8a was treated with SmI 2 , no reaction occurred.…”
Section: Resultsmentioning
confidence: 93%
“…It was underlined that the isoxazolidine ring remained intact during the N‐deprotection step with the aldehyde function still masked under a cyclic pseudo‐acetal form. For instance, aspartic aldehyde derivatives (R = CH 2 CO 2 Alk, Figure 1) were obtained by using either chiral aspartic nitrones5b or chiral vinyl ethers5c in efficient exo and asymmetrically controlled 1,3‐DC reactions 7…”
Section: Introductionmentioning
confidence: 99%